Algoritmização das relações sociais em rede, produção de crenças e construção da realidade - Caribé, João Carlos Rebello (2019)
This research aims to understand, from the dismemberment of the information’s concept, to the construction of a conceptual model, how the individual and groups process information, how it is mediated and assimilated. The proposal involves the understanding of the process of algorithmization of networked social relations, and the processing of information by individuals and groups, for the production of beliefs and construction of reality. The main motivation for this study is to understand how phenomena such as bubble filter, modulation and surveillance influence this process, and what are they affect the society.